Power and landscape in Atlantic West Africa : archaeological perspectives - Monroe, J. Cameron; Ogundiran, Akinwumi (Cambridge University Press, 2012)
"This volume applies insights drawn from the theories and methods of landscape archaeology to contribute to our understanding of the nature if West African societies in the Atlantic Era (17th-19th Centuries AD). The authors adopt a broad set of methods and approaches to tackle how the nature and structures of African political and social relations changed across regions in this period. This is only the second volume in a decade to focus on the archeology of this period in West Africa, and the first volume in sub-Saharan Africanist archeology to be focused in the recent past in one sub-region of the continent from a coherent methodological and theoretical standpoint"--Provided by publisher.